Cyclin D1 expression and novel mutational findings in Rosai‐Dorfman disease. (6th June 2019) - Baraban, Ezra; Sadigh, Sam; Rosenbaum, Jason; Van Arnam, John; Bogusz, Agata M.; Mehr, Chelsea; Bagg, Adam
Summary: Rosai‐Dorfman disease (RDD) is an enigmatic histiocytic disorder classically diagnosed by a distinctive combination of pathological features: emperipolesis, or migration of intact haematological cells through the voluminous cytoplasm of lesional histiocytes, and expression of S100 by these histiocytes. The pathogenesis has long been elusive until the recent detection of recurrent and mutually exclusive mutations in several oncogenes in the mitogen‐activated protein kinase (MAPK) pathway. Based on these findings, we investigated a cohort of 21 RDD patients and found that the lesional histiocytes in 86% (18/21) of patients exhibited strong and diffuse nuclear Cyclin D1 expression, which not only may provide a diagnostic marker for this sometimes pathologically challenging disease, but also probably reflects constitutive MAPK pathway activation because we additionally identified phosphorylated‐ERK expression in 90% (19/21) of cases. Further, we performed massively parallel sequencing on a subset (6/18) of the CyclinD1 positive cases, identifying several mutations that have not been previously reported in RDD. Taken together, our findings bolster the concept of RDD as a disease of MAPK activation in a substantial percentage of cases and enhance the current understanding of the pathogenesis of RDD.